The Role of Social Support Related to Government Budget Efficiency on the Impact of Job Satisfaction and Motivation on Employee Performance in Aceh - Rahmat Arfan; Fitrian Rizky (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study seeks to examine and evaluate job satisfaction as a moderating variable that affects the relationship between job satisfaction, motivation, and employee performance in the context of the government's budget efficiency policy implementation in Aceh.  In light of the present government budget efficiency policy, the performance of Aparatur Sipil Negara (ASN) staff is a pivotal element in attaining this efficiency.  Optimal employee performance not only facilitates the achievement of corporate objectives but also ensures the effective and efficient utilization of available funds.  This research population comprises all ASN personnel, including both Pegawai Negeri Sipil (PNS) and Government personnel with Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) under the Satuan Kerja Perangkat Aceh (SKPA).  This study used purposive sampling in conjunction with incidental sampling strategies, given the substantial population size.  This sampling approach is selected for its practicality in identifying respondents when the overall population size is indeterminate.  Respondents were randomly chosen throughout the data collection phase in June-July 2025.  The Moderated Regression Analysis (MRA) method was employed for data analysis to evaluate hypotheses. This study's findings indicate that job happiness and work motivation significantly influence employee performance.  A multiple linear regression model indicates that job happiness adversely and significantly affects employee performance, whereas work motivation positively and significantly influences employee performance.  In contrast, the MRA model reveals a substantial and inverse interaction effect between job satisfaction and motivation on employee performance.  Social support serves as a moderator that enhances the positive and considerable impact of job satisfaction and motivation on employee performance, particularly in relation to budget efficiency implementation in Aceh.  Consequently, organizational management within all SKPAs in Aceh must prioritize enhancing social support in the workplace as a fundamental strategy to alleviate the adverse impacts on job satisfaction and optimize the beneficial effects of work motivation on employee performance.  This strategy will not only enhance the work environment but also improve human resource efficacy in addressing problems posed by the budget efficiency policy, therefore fostering optimal and sustainable performance.